Los orígenes del apoyo presupuestario en la evolución de la ayuda contemporánea - Wood, Marta; Boza, José; González, Matías; De-León-Ledesma, Javier (Revista Iberoamericana de Estudios de Desarrollo)
Budgetary support dates back to relatively recent times, when the interest in this type of aid emerged during the last decade. However, budgetary support, seen as a fund transfer from a country or organization to other recipient country to help them with their national budgets, appeared earlier. In this sense, this paper reviews this type of aids from the 50s —when the decolonization process started— to our days. Since that decade some key elements have appeared and they have led to the concept of budgetary support as it is known today. The main elements are the fight against poverty —as the main goal—, the change of approach about the conditionality of aids and the valuation of the trust-based relationships between benefactors and recipients.